Transnational religion and fading states - Rudolph, Susanne Hoeber (Westview Press, 1997)
Focusing on the dilution of the state sovereignty, this book examines how the crossing of state boundaries by religious movements leads to the formation of transnational civil society. Challenging the assertion that future conflict will be of the "clash of civilizations" variety, it looks to the micro-origins of conflicts, which are as likely to arise between states sharing a religion as between those divided by it and more likely to arise within rather than across state boundaries. Thus, the chapters reveal the dual potential of religious movements as sources of peace and security as well as of violent conflict